39 microlectures : in proximity of performance - Goulish, Matthew, 1960- (London ; New York : Routledge, 2000)
39 Microlectures: In Proximity of Performance is a collection of miniature stories, parables, musings and thinkpieces on the nature of reading, writing, art, collaboration, performance, life, death, the universe and everything.
Book Cover; Title; Contents; Acknowledgements; Introduction; What is a microlecture?; Repetition; Criticism; Pedagogy; Beginnings; Hair; Women and directing; Technologies of dying; How does a work work where?; The kaleidoscopic self; Three noteworthy departures; Failure; To the reader-2; Source Notes; Bibliography; Introduction to the Index; Index.
Includes bibliographical references (pages 197-203) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Performance art; Manœuvre artistique; LITERARY CRITICISM -- American -- General; Performance art; Electronic books; Electronic book